Evaluating the impacts of climate change on streamflow in srepok watershed - Khôi, Đào Nguyên (Vietnam Journal of Earth Sciences, 2014)
In this paper, the author investigated the effects of climate change on streamflow in Srepok watershed. The climate change scenarios were built by downscaling method (delta change method) based on the outputs of MIROC 3.2 Hires GCM. The SWAT (Soil and Water Assessment Tool) model was used to investigate the impacts on streamflow under climate change scenarios. The calibration and validation results showed that the SWAT model was able to simulate the streamflow well. Their difference in simulating the streamflow under future climate scenarios was also investigated.Results indicated a 1.3-3.9oC increase in annual temperature and a -4.4 to -0.5% decreases in annual precipitation corresponded to a decrease in streamflow of about -7.6 to -2.8%. The large decrease in precipitation and runoff are observed in the dry season.